Forest Management, Conflict and Social-Ecological Systems in a Changing World - Fernández-Manjarrés, Juan F.; Sansilvestri, Roxane (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Conflicts in forest management are unavoidable because of the large temporal and spatial scales characteristic of forests ecosystems and the large number of actors involved. Forests are multifunctional ecosystems par excellence, and it can be hypothesized that current public policies, and especially those labeled as societal transitions, can affect this widespread holistic management goal. In this Special Issue, the different contributions by the authors raise the questions of how different types of conflicts arise and what alternatives exist to solve those conflicts. The Issue contains examples from both temperate and tropical forests and addresses, for instance, conflicts arising from REDD+ programs, the declaration of new protected areas, the complexity of negotiating carbon offset targets, the loss of local knowledge because of demographic trends, and meeting biodiversity and biomass targets simultaneously, among others. We present a general typology of sources of conflicts because of two dimensions: a vertical dimension represented by bottom-up versus top-down approaches and a horizontal dimension arising by ecosystem extent and ownership boundaries. Awareness that new policies can be a source of unexpected conflicts calls for precaution while testing new 'transition' approaches.